Epidemiology and genetic diversity of common human coronaviruses in Beijing, 2015-2023: A prospective multicenter study - Qi Huang; Lu Kang; Xiaofeng Wei; Cheng Gong; Hui Xie; Maozhong Li; Yiting Wang; Mei Dong; Fang Huang (International Journal of Infectious Diseases, 2025)
ABSTRACT: Objectives: To investigate the epidemiological and genetic features of common human coronaviruses (HCoVs) in Beijing in the context of the COVID-19 pandemic. Methods: We collected clinical samples from patients with acute respiratory tract infections (ARTIs) in 35 sentinel hospitals from 2015 to 2023. HCoVs were detected via multiple real-time PCR, and S gene sequencing and phylogenetic analysis were subsequently performed. Results: From 2015 to 2023, the combined detection rate of HCoVs was 1.55% (909/58,550). During the COVID-19 pandemic, a significant increase in HCoVs detection was observed (P < 0.001). Overall, the epidemic season of four HCoVs was from July to October, and each HCoV showed different epidemic seasons. Notably, HCoV-NL63 and HCoV-229E exhibited pronounced annual alternations in prevalence. The highest combined detection rates of HCoVs were in the ≥60 years age group (1.85%), followed by the 0-5 years age group (1.48%). HCoV-229E was more prevalent in patients with severe community-acquired pneumonia (sCAP) (P = 0.001). Phylogenetic analyses revealed that the four HCoVs were subjected to negative selection pressure, and multiple high-frequency amino acid site mutations were observed. HCoV-229E formed an emerging lineage after 2021. Conclusions: This nine-year multicenter study in Beijing systematically elucidated that the four HCoVs exhibit distinct epidemiological characteristics, susceptible populations, and common mutations in amino acid sites, especially in the context of COVID-19. Therefore, continuous epidemiological surveillance and genetic characterization studies are imperative for predictive warning and timely identification of emerging coronavirus.